COMPLEX OF Co(II) WITH LIGAND 2,2’-BIPYRIDINE AND ANIONIC TRIFLUOROACETATE: SYNTHESIS, PHYSICAL PROPERTY, STRUCTURAL ANALYSIS AND ITS ANTIBACTERIAL ACTIVITY - Laksono, Endang Widjajanti; Astuti, Nofianti Vivi; Yunita, Isti; Sugiyarto, Kristian Handoyo (Malaysian Journal of Science, 2024)
The complex containing Co(II), bipyridine (bipy), and trifluoroacetate (TFA) was prepared and characterized. The metal content, conductance, and TGA-DTG analysis estimate the formula of [Co(bipy)3](CF3COO)2.5,5H2O. The magnetic property shows the moment of 4.2-5.3 BM which should correspond to the three unpaired electrons with the typically strong orbital contribution in cobalt(II). The UV-VIS spectral profiles indicate the three possible spin-allowed transitions of the corresponding quartet states. The characteristic vibration modes of bipy and TFA confirm the complex formula. The SEM photographs support the crystalline particle size, and the corresponding EDX signifies the existence of all elemental contents. The powder XRD profile has been refined according to the Le Bail method of the Rietica program, and the result suggests being a structurally monoclinic system of space group C2/c. This complex exhibits a weak inhibition against S. aureus and E. coli bacterial activity.